Publisher Correction: Sudden emergence of human infections with H7N9 avian influenza A virus in Hubei province, central China - Jiafa Liu (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.